RESPON PERTUMBUHAN Hedychium borneense R.M. Sm. (Zingiberaceae), TUMBUHAN ENDEMIK DAN SEMI-EPIFIT DARI KALIMANTAN DENGAN PERBEDAAN MEDIA TANAM - Trimanto Trimanto; Destario Metusala; Suhartono Suhartono (Jurnal Pro-Life, 2019)
Information on the type of appropriate growing media for plant species in Zingiberaceae family has not been widely provided. This study aimed to examine the effect of several types of growing media on the growth of Hedychium borneense, an endemic and semi-epiphytic Zingiberaceae from Kalimantan. The study was conducted in a completely randomized design and the data has been analyzed using anova 1 way test. The results showed that the type of growing media gave a significant effect on plant height and number of shoots (tillers), but did not affect the number of leaves. The best growing media for the highest plant height average were sphagnum moss and sand + compost. These two types media, sphagnum moss and sand + compost, also give more shoots significantly compared to the other media. The highest life percentage is showed by the sphagnum moss media with 100% rate of life. Therefore, sphagnum moss and mixing media between sand + compost (1: 1) are the best growing media for semi-epiphytic H. borneense plants. Keywords: Epifit, Media Tanam, Hedychium borneense, Zingiberaceae.